Process improvement and microbial characterisation of biological nitrogen removal for tropical wastewater with low chemical oxygen demand/nitrogen ratio / How Seow Wah - How , Seow Wah (2020)
Malaysia has one of the most established biological nitrogen removal in wastewater treatment plants (WWTPs) among the developing Southeast Asian countries. The current WWTPs’ design and operating guidelines in Malaysia are mainly derived from other developed countries with more experiences in operating biological nitrogen removal. These design guidelines are good practices for WWTPs in the temperate climate region, but may not be optimal for the local wastewater characteristics and tropical climate in Malaysia. The local wastewater industry is keen to improve the design and operation of WWTPs to reduce the energy consumption and operating cost, which helps to foster a more cost-effective and sustainable industry. However, a complete understanding on the local wastewater conditions, such as the detailed characteristics and microbiology of tropical systems, are still lacking. This project aimed to develop an improved biological nitrogen removal in treating local wastewater. To achieve this aim, detailed wastewater characterisation were performed to formulate operating strategies for a low-cost biological nitrogen removal. The operating strategies were tested in lab-scale reactors. The microbial community were also investigated to understand the effects of these operating strategies on the microorganisms. In the wastewater characterisation study, wastewater from six WWTPs in Kuala Lumpur was sampled to characterise their organic and nitrogen content. The results showed that soluble fraction of the tropical wastewater samples had low chemical oxygen demand-to-nitrogen ratio (COD/N). COD fractionation experiment further revealed that the readily-biodegradable COD (rbCOD) content was low, while slowly-biodegradable COD (sbCOD) from particulate settleable solids (PSS) in the wastewater was the main source of biodegradable COD. The hydrolysis rate of PSS was accelerated in tropical temperatures (30 ± 2°C) to provide sbCOD for denitrification. Based on these wastewater characteristics, the low rbCOD content may be conducive for nitrification under low-dissolved-oxygen (low-DO) condition (< 1 mg O2/L) to reduce aeration energy. Also, sbCOD in the wastewater may be utilised to enhance the denitrification performance. Batch experiments demonstrated active nitrification at low-DO concentration (1 mg O2/L). When low-DO nitrification (0.9 ± 0.1 mg O2/L) was applied in a reactor, high ammonia removal efficiency (93 ± 6%) was achieved. Furthermore, utilising sbCOD in the post-anoxic stage of an oxic-anoxic (OA) reactor reduced the effluent nitrate concentration below the discharge limit in Malaysia. The recommended hydraulic retention time and sludge retention time (SRT) of the low-DO OA reactor developed in this study was 16 h and 20 d, respectively. Microbial analyses of the low-DO OA reactor showed that long SRT (20 d) promoted the growth of nitrifiers affiliated with Nitrospira to achieve a stable low-DO nitrification performance. Operating a low-DO OA process could reduce the WWTPs’ energy consumption by 20% when compared with the existing process design. A better understanding on the local wastewater conditions in this study, such as detailed characteristics and process microbiology, led to the development of a low-DO OA process. The low-DO OA process was an improved biological nitrogen removal in treating low COD/N tropical wastewater, which could help to encourage a more energy-efficient and cost-effective wastewater industry in Malaysia.